Pemanfaatan Artificial Intelligence (AI) dalam Proses Pembelajaran IPA di Kelas Rendah pada Tema Panca Indra untuk Memotivasi Siswa UPT SDN 01 Mekar Laras - Siti Ardina Mutia; Nuri Yanti; Seila Ananda Hidayah; Juwita Tri Handini; Dhia Asy Syafa (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the use of Artificial Intelligence (AI) in Natural Science learning on the five senses material and describe the learning motivation of students in the lower grades of UPT SDN 01 Mekar Laras. The study used a descriptive qualitative approach with research subjects of second-grade teachers and students who were selected purposively because they were directly involved in AI-assisted learning. Data were collected through observation of the learning process, interviews with teachers and students, and documentation. Data analysis was carried out using the Miles, Huberman, and Saldaña model which includes data condensation, data presentation, and drawing and verifying conclusions. The results showed that the use of AI in science learning created a more interactive, interesting, and enjoyable learning atmosphere. Students appeared more enthusiastic, actively participated in learning activities, and showed a higher interest in the five senses material. Teachers also utilized AI as a medium to present material in a more varied and easy-to-understand way. These findings indicate that the use of AI can support the creation of a more meaningful learning experience and encourage the emergence of student learning motivation in science learning in lower grades.